Real-time transient stability assessment using stacked auto-encoders. Issue 4 (11th August 2020) - Azarbik, Masoud; Sarlak, Mostafa
Abstract : Purpose: This paper aims to report how one can assess the transient stability of a power system by using stacked auto-encoders. Design/methodology/approach: The proposed algorithm works in a power system equipped with the wide area measurement system. To be more exact, it needs pre- and post-disturbance values of frequency sent from phasor measurement units. Findings: The authors have investigated the performance of the proposed method. Going through details, the authors have simulated many contingencies, and then have predicted the transient stability in each of which by using the proposed algorithm. Originality/value: The results demonstrate that the algorithm is fast, and it has acceptable performance under different circumstances including the change of system topology and failures of telecommunication channels.